Perception and Challenges Integrating Teaching English Based on LMS Moodle During Covid-19 Pandemic - Rizky Eka Prasetya (ELITE JOURNAL, 2021)
LMS Moodle has been the primary online-mediated Teaching in Higher Education in the pandemic era. The unexpected pedagogical struggled to adapt conventional class to the virtual class, particularly English teaching. Various investigations have been conducted to examine and describe the perception and challenges lecturers face in eLearning. On the contrary, the lecturers need to the presentable course in Moodle for their students. The purpose of the study investigates the lecturer's perception and the challenge of utilization in Moodle-based English teaching. A descriptive qualitative design was applied to the study. Questionnaires and semi-structured interviews were obtained from 54 lecturers to collect the data. Technology Acceptance Model (TAM) concentrates on divining and evaluating lecturers' fundamental pre-acceptance of LMS Moodle. Close-ended questions practiced receiving the population of the analyzed topics. While open-ended questions were applied to gain the lecturers' perception of Moodle-based implementation topics. Subsequently, the finding of the result is to enhance the perspective and solve the challenges in teaching English Moodle-based.